Peranan Manajemen Perencanaan dalam Meningkatkan Kualitas Pelayanan Kesekretariatan pada Kantor Camat Hiliran Gumanti Kabupaten Solok - Hane Johan; Halendra Halendra (JURNAL PUNDI, 2020)
The purpose of this research [is] 1. To know how role of planning management in improving the quality of service of secretariat [at] Office Sub-Regency Chief Fistula of Gumanti Sub-Province of Solok 2. To know constraints what met in role of planning management in improving the quality of service of secretariat [at] Office Sub-Regency Chief Fistula of Gumanti Sub-Province of Solok.As for this research internal issue formula [is] 1. How Role Of Management Planning In Improving the Quality Of Service Of Secretariat [At] Office Sub-Regency Chief Fistula of Gumanti Sub-Province of Solok 2. Any kind of constraint met in Role Of Management Planning In Improving the Quality Of Service Of Secretariat [At] Office Sub-Regency Chief Fistula of Gumanti Sub-Province of Solok Data which [is] writer get in this research metede [is] data of kulitatif. Role of planning management in improving the quality of service of secretariat [at] Office Sub-Regency Chief Fistula of Gumanti Sub-Province of Solok important so central, because with existence of planning management [in] Office Sub-Regency Chief Fistula of Gumanti Sub-Province of Solok very assisting of service facet, good that prima service and also service of public.Constraints in role of planning management in improving the quality of service of secretariat [at] Office Sub-Regency Chief Fistula of Gumanti Sub-Province of Solok, constraint which [in] temuai [is] Resource of Aparatur, Facilities And Basic Facilities, Awareness of Society, Far it[him] apart [among/between] sub-regency chief office with settlement of resident. Everything which [in] planning surely always there [is] constraints which [in] facing, and which we [do/conduct] will not always smoothly, surely always there [is] barricade, remain how us make that constraints can overcome better, so that planning of us also walk better as according to what wanted.